Social entrepreneurship as internally driven development - Ismail, Yusof; Mhd. Sarif, Suhaimi; Ishak, Mohd Izzuddin (Pusat Pengembangan Integrasi Ilmu Naqli & Aqli (PIINA), 2017)
Serving a community is reflected in the concept of Tawhid (Oneness of God) notwithstanding the faith and race of the target community to be served. Tawhid embraces entire humanity; it considers human races as belonging to the same great-great grandparents, Adam and Eve. Humanity may be served through available channels, including social entrepreneurship. Although the paper is motivated by Tawhid as the foundation of social entrepreneurship, the benefits of engagement in the social entrepreneurship initiatives may well serve Muslims and non-Muslim public alike. While the engagement in social entrepreneurship may be faith-driven, it in no way interferes with the faith of the non-Muslim beneficiaries of the project or non-Muslim associates. As a concept, varying levels of engagement in social entrepreneurship by Muslims are internally-driven, a self-development contributing towards social development.